EVALUASI PENERAPAN IDENTIFIKASI PASIEN DI BANGSAL RAWAT INAP RSI SITI AISYAH MADIUN - Donna Dwi Yudhawati; Ekorini Listiowati (Universitas Muhammadiyah Yogyakarta, 2015)
Backgraund: This research is to reveal the evaluation of the application of identification patient at Siti Aisyah Madiun Islamic Hospital. The diversities and the routines of the services in hospital will make adverse event (KTD) if we don’t manage it properly. Errors due to misidentification patient happen almost in every aspect or diagnosis stages and treatment, so it needs the accuracy of patient’s identifications. Method: This research using qualitatif methods that produce descriptive data such as written words and verbal from people and observed attitude and study planning cases that exploits a problem with detail data retrictions, accompanied with detail data retrieval from many sources so can reflects patient identifications done by Siti Aisyah Islamic Hospital. Instruments used in this research is the search guidelines, in-depth interviews, FGD and RCA. Result and Discussion: This research result shows incident type of patient safety happens at Siti Aisyah Islamis Hospital. One of the causes is misidentifications patients. The nurses knowledge about the identification of patients had 100 % but the implementation of identification in hospital not optimal. Conclussion: The implementation of the identification of patients that should be done by nurses not yet become a culture in Siti Aisyah Madiun Islamic Hospital and the implementation still far from the expectation. The suggestion from the researchers is management should do some evaluation and routine monitoring on the patient’s identifications in hospital to cultivate all nurses to identify patients become common culture nurse.